Anemia pada Pasien Tuberkulosis - Inna Kurniaji; Waluyo Rudiyanto; Indri Windarti (CV. Jasa Sukses Abadi, 2023)
Tuberculosis (TB) is one of the most common causes of health problems in the world. The prevalence of TB in the world is estimated at 10.6 million, and 1.6 million of them died from TB, in Indonesia the incidence of TB reached 503,712. Tuberculosis is a chronic infectious disease caused by Mycobacterium tuberculosis, which is known to cause complex hematological disorders. The hematopoietic system is thought to be affected during TB infection, so that Hb levels tend to decrease along with bacterial increase, which eventually causes anemia. The article aims to determine the incidence of anemia in TB patients and the mechanism of anemia in TB patients. Based on the results of a literature review conducted on references found from 2012–2022, it shows that anemia is a common condition in TB. The mechanism that causes anemia in TB patients is due to its pathogenesis as a chronic inflammatory disease. Anemia is an indicator in providing clues to diagnosis, prognosis, complications and response to TB therapy. Nutritional intake and adherence to TB therapy need to be done properly to prevent the development of severe disease and improve the patient's quality of life.